Extending the depth of focus of fiber-optic optical coherence tomography using a chromatic dual-focus design - Li, Jinhan (2020)
We report a dual-focus fiber-optic probe designed to extend depth of focus (DOF) in high-resolution endoscopic optical coherence tomography. We exploited the broad spectral bandwidth of a supercontinuum source and, in the fiber probe, the foci of the 750-1000 nm and 1100-1450 nm inputs were axially chromatically shifted. The interference signals from the two spectral bands were measured with a Si camera-based spectrometer and an InGaAs camera-based spectrometer, respectively. We verified the feasibility of the design using a phantom composed of microparticles and swine small intestine tissue ex vivo. The results showed that a transverse resolution below 5 μm over 300 μm could be maintained, and that the extended DOF was 2 times larger than that of the single focus probe via the use of dual spectral band inputs and a chromatic focal shift.